Deteksi Dini Tumbuh dan Kembang Balita Sesuai Standar Pelayanan Minimal Posyandu - Fitriahadi, Enny; Widagdo, Laksmono (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2013)
Most of the morbidity and mortality of children under five in Indonesia reached 44 per 1000 live births in which one is due to malnutrition, malnutrition rate increases that would have an impact on morbidity and mortality. The purpose of this study to analyze the factors related to the behavior of the minimum service posyandu child’s weight in posyandu Puskesmas South Cilacap I Cilacap. This type of research using quantitative methods with cross sectional approach. The study population was all posyandu which is in the South Cilacap Health Center I, which totaled 344 Cilacap district posyandu. Study sample totaled 185 posyandu defined by using simple random sampling. Data obtained by interview using a questionnaire and analyzed by univariate, bivariate and multivariate analyzes. The findings indicate that knowledge of cadres, cadres attitude towards the minimum service in posyandu child’s weight is a variable that affects the behavior of the minimum service posyandu child’s weight. Conclusions from this study illustrate that the question before the current knowledge and growth monitoring sessions have a relationship between the behavior of cadres with minimal service child’s weight.